The effect of different bonded retainer wires on tooth mobility immediately after orthodontic treatment - Kučera, Josef; Marek, Ivo; Littlewood, Simon J (European journal of orthodontics, 2022)
OBJECTIVES: This study aimed to compare the immediate influence of four commonly used retainer wires on tooth mobility following orthodontic treatment with fixed appliances. MATERIALS AND METHODS: Eighty patients after orthodontic treatment were assigned to four study groups (n = 20 in each group). Groups were provided with directly bonded fixed retainers-0.0150′′ (group A), 0.0175′′ (group B), 0.016 × 0.022′′ (group C), and 0.0215′′ (group D). Tooth mobility was measured using the Periotest device at two times-after removal of fixed appliance (T1) and after bonding of the retainer (T2). Values of tooth mobility, 'Periotest values', were analysed between groups and compared with the physiologic tooth mobility in a control group of untreated patients (n = 65). Kruskal-Wallis H, Mann-Whitney U, Dunn's test, Fisher's exact test, and binary logistic regression tests were used to analyze the data. RESULTS: Tooth mobility after orthodontic treatment was significantly increased. While canines remained within normal range of tooth mobility, values for incisors increased on average to the first degree of tooth mobility (slight mobility). Logistic regression analysis identified age as a significant predictor for increased tooth mobility (P = 0.032) with odds ratio 1.065 (95% CI 1.005-1.128), with mobility increasing with age. After bonding of the retainer in all four groups, the tooth mobility was reduced to values which were not significantly different form normal physiological values found in the control group (P > 0.05). There were no differences in the amount of change or in tooth mobility values at T2 between the different types of bonded retainers. LIMITATIONS: Age of subjects in the control group was significantly higher than that in the study groups. An alternation method was used instead of randomization to distribute the four different types of retainers. CONCLUSIONS: All of the retainer wires were able to successfully reduce the increased tooth mobility caused by orthodontic treatment to normal levels. The values of tooth mobility after placement of retainers were within the range of physiologic tooth mobility.
Keywords: Orthodontic Appliances, Fixed; řezáky; Orthodontic Appliance Design; ortodontické retainery; ortodontické přístroje - design; Orthodontic Retainers; lidé; fixní ortodontický aparát; viklavost zubů; Tooth Mobility; Incisor; Humans